A study of employee satisfaction in two manufacturing facilities of General Motors South Africa - Matutoane, Leanetse Paul (Rhodes University, Faculty of Commerce, Investec Business School, 2009)
Employed individuals spend a majority of their waking time at work. Therefore, within an individual's working lifetime, most hours will be spent at work. Subsequently, theories abound purporting that humans are hedonistic beings. Considering that on average people spend most of their working lives in a working environment, it then stands to reason that people should endeavor to be satisfied at work if humans are always in pursuit of happiness. The questions arise as thus: what makes people satisfied at work, does being satisfied with the job result in less turnover, and is that the only reason that they would endeavor to prolong their employment, are older employees more satisfied with their jobs than younger employees, is a plant with an older workforce more satisfied than a similar plant with a younger workforce? This study attempts to find an answer to these and other related questions. It was conducted on employees of two plants of an automotive manufacturer based in Port Elizabeth, a town in the Eastern Cape province of South Africa. The Job Descriptive Index (JDI) was used to collect the feelings of 92 employees in different shops and analyzed to check for differences in satisfaction levels. No significant differences were found between the plants, shops and age categories surveyed.
Keywords: General Motors Corporation -- South Africa -- Port Elizabeth; Job satisfaction -- South Africa -- Port Elizabeth; Employee motivation -- South Africa -- Port Elizabeth; Employee attitude surveys -- South Africa -- Port Elizabeth